Inequalities in mammography and Papanicolaou test coverage: a time-series study - Malta, Deborah Carvalho; Prates, Elton Junio Sady; Silva, Alanna Gomes da; Santos, Filipe Malta dos; Oliveira, Greice de Campos; Vasconcelos, Nádia Machado de; Cristo, Elier Broche (São Paulo Medical Journal, 2020)
BACKGROUND: Cancer is a serious public issue problem worldwide. In Brazil, breast cancer is the most common type and cervical cancer is the third most frequent among women. OBJECTIVE: To analyze the temporal trend of coverage of mammography and cervical oncotic cytological testing, between 2007 and 2018. DESIGN AND SETTING: Time-series study conducted in the 26 Brazilian state capitals and in the Federal District. METHODS: A linear regression model was used to estimate trends in coverage of mammography and cervical oncotic cytological testing over the period. The data collection system for Surveillance of Risk and Protection Factors for Chronic Diseases by Telephone Survey (Vigitel) was used. RESULTS: A significant increase in mammography coverage was observed, from 71.1% in 2007 to 78.0% in 2018. There was a trend towards an increase among women with 0 to 8 years of schooling, in all regions of Brazil. Regarding cervical oncotic cytological testing coverage, there was a trend towards stability during the period analyzed, reaching 81.7% in 2018. On the other hand, there was a significant increase in the northern region. CONCLUSIONS: There was an improvement in the coverage of these screening examinations, especially regarding mammography. However, it is still necessary to expand their provision, quality and surveillance, aimed towards women’s health.